Investigation of atm propulsion force-time profiles using functional data analysis on front crawl sprint swimmers - Sacilotto, G. B. D.; Warmenhoven, J. S.; Mason, B. R.; Ball, N.; Clothier, P. J. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
The purpose of this investigation was to assess whether characteristics of the Assisted Towing Method (ATM) propulsive force-time profiles can discriminate between elite and sub-elite male sprint swimmers. Eleven elite and seven sub-elite sprint front crawl swimmers completed the ATM protocol to capture propulsion force-time profiles. The second full stroke cycle taken from the median propulsion trial on both the right and left arms were selected and functional data analysis was used to process the trials. Functional principal components analysis (fPCA) results revealed a statistical difference between the elite and sub-elite groups (p > 0.000). Further, within the elite group profiles, a distinctive double peak was found. The double peak profile could suggest a more efficient and effective stroking ratio of active drag and propulsion within the elite group.